[Ln4] complexes based on 8-hydroxylquinoline-schiff base: Synthesis, crystal structure and near-infrared emission. (1st June 2021) - Gou, Jian; Yang, Qian-Qi; Li, Si-Yu; Zhao, Li-Hua; Gao, Hong-Ling; Cui, Jian-Zhong
Graphical abstract: In this article, six rare earth complexes based on 8-hydroxylquinoline-schiff base (HL = 5-(2-furanimino)-8-hydroxylquinoline) were synthesized and characterized. Notably, complex 3 emits characteristic near-infrared luminescence of the corresponding Er 3+ ions when excited by ultraviolet spectrum of 350 nm, which demonstrates the efficient energy transfer from the excited triplet states of the ligands to the central Er 3+ ions. Abstract: Five lanthanide-containing complexes, featured with the structural formula of [Ln4 (L1 )4 (L)6 ( μ 3 -OH)2 ]·m(CH3 CN) and a related binuclear Yb-based complex, were synthesized and structurally characterized (HL = 5-(2-furanimino)-8-hydroxylquinoline; HL1 represents for β -diketone ligand). The solid-state near-infrared fluorescence was also tested. Complex 3 emits characteristic near-infrared luminescence of the corresponding Er 3+ ions when excited by ultraviolet spectrum of 350 nm, which demonstrates the efficient energy transfer from the excited triplet states of the ligands to the central Er 3+ ions.